Lived Experiences of Neurodiverse Students: A Review - Victor-Aigbodion, Vera; Eseadi, Chiedu (COUNS-EDU: The International Journal of Counseling and Education, 2023)
This study aims to examine available literature on neurodiversity, particularly as it relates to neurodiverse students’ lived experiences. This study utilized the scoping review method to effectively map how research about neurodiverse students has been designed and conducted. Through a thorough search of four databases, articles were selected for data extraction and review based on the named criteria. Among all the studies reviewed, one of the themes that stood out was the view that only a few research directly assessed the needs of students with neurodiversity. It is also worth noting that of all kinds of neurological conditions, Autism Spectrum Disorder and Asperger Syndrome received due attention among all the papers about neurodiversity. Autism Spectrum Disorder (ASD) and high-functioning autism received greater attention, followed by Asperger syndrome. Research efforts concerning the lived experiences of neurodiverse students are limited, particularly in Africa, where this research found no article that captured the lived experiences of neurodiverse students from their perspectives. These findings build on existing research by ascertaining whether neurodiverse students’ voices are acknowledged enough by researchers who could influence inclusion in academic planning, curriculum design, social activities and general academic life. Findings from this research imply that it would be of utmost assistance to researchers if gaps in neurodiversity research are identified to inform ideas for future research. Future studies ought to focus on African countries to explore the situation and academic life of neurodiverse students and not merely depend on the input of teachers, parents and neurodiversity professionals.